The First Original Copy and the role of blockchain in the reproduction of cultural heritage - Ch’ng, Eugene (Massachusetts Institute of Technology Press, 2019)
The First Original Copy refers to any first true 3D facsimile of digitally reproduced physical object. The notion of a copy being the first and original implies that it is unique and therefore the approach used for managing rights and ownership influences its value. Whilst virtual goods traded within virtual worlds are subject to rules and policies, the production of digital objects in the real world does not have a mechanism from which rarity and uniqueness can be guaranteed. Digital copies are subject to further copying and thus, the value of even an exact copy can never be perceived to be equivalent to its original. Through what means can we imbue 3D reproductions of cultural objects with value that is at least asymptotic to their originals? There may be a candidate solution. Discussed in this paper is a possible approach for resolving a long-term issue related to authenticity, ownership, perpetuity and the quantitative tracking of value associated with 3D copies. Blockchains essentially bring the systemic management of virtual objects within virtual worlds into the real world. This forum article examines the candidate solution by answering the questions above, and discusses the issues associated with the concept of the First Original Copy.